2020
DOI: 10.1016/j.bbadis.2019.165591
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and pathogenesis of maternal-fetal transmission of Trypanosoma cruzi and a case for vaccine development against congenital Chagas disease

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 189 publications
(218 reference statements)
1
28
1
2
Order By: Relevance
“…The protection was associated with increase of CD8 + T cell proliferation and IFN-γ production [31,32]. However, these same candidates did not control cardiomyopathy in chronically infected mice or dogs (reviewed in [18,33]). DNA therapy encoding ASP2 and TS (individually or in combination) offered no protection against parasite burden, mortality, and cardiomyopathy in infected mice [15,30], despite their known efficacy as a prophylactic vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The protection was associated with increase of CD8 + T cell proliferation and IFN-γ production [31,32]. However, these same candidates did not control cardiomyopathy in chronically infected mice or dogs (reviewed in [18,33]). DNA therapy encoding ASP2 and TS (individually or in combination) offered no protection against parasite burden, mortality, and cardiomyopathy in infected mice [15,30], despite their known efficacy as a prophylactic vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…This immunotherapeutic vaccine not only would allow targeting different humoral and cellular elements as well metabolic pathways but also would be able to reduce doses and drug exposure periods, thus contributing to the decrease in toxic effects and minimization of the emergence of drug resistance. Not to be underestimated, as has been recently reviewed by Rios et al ( 61 ) and proposed by Dumonteil et al ( 62 ), therapeutic vaccines could be an excellent tool to avoid future congenital transmission, which is estimated at 5% in Latin America, preventing the risk of pregnancy complications like preterm rupture of membranes and preterm delivery. Although available drugs are not approved for use during pregnancy, several studies suggest that reducing maternal parasitemia before conception reduces the risk of congenital transmission ( 63 65 ), and it was recently estimated that a therapeutic vaccination of Chagas-positive pregnant women would be cost-effective and cost saving ( 66 ).…”
Section: Discussionmentioning
confidence: 97%
“…Together with adjuvant E6020, Tc24 showed that 60% of therapeutically vaccinated mice had undetectable levels of parasite and decreased cardiac fibrosis. Greater efficiency was also observed in the therapeutic vaccine TG2/TcG4 in infected animals that overexpressed glutathione peroxidase and that were able to control oxidative damage responses 20,22,24 .…”
Section: Vaccine Development Against Trypanosoma Cruzi and Chagas Dismentioning
confidence: 95%
“…Other antigens that do not belong to large families and that have been tested for their antigenic potential include the complementary regulatory protein (CRP or gp160); the lysosomal cysteine proteinase called cruzipain (60kDa); the calcium flagellar binding proteins FCaBP or Tc24 (24kDa) and GP82 (82kDa); the kinetoplastids membrane proteins KMP-11 (11kDa) and LYT1 (61kDa), and the paraflagellar rod proteins (70-86kDa) and TC52 (52kDa). Along with vaccine candidates, multiple adjuvants, administration routes, concentration and number of doses, and prime boost strategies are also being tested to change immune responses induced by the Th1 vaccine and improve long-term protective efficacy 20,22 .…”
Section: Vaccine Development Against Trypanosoma Cruzi and Chagas Dismentioning
confidence: 99%